Impact Of Aerobic Biostabilisation And Biodrying Process Of Municipal Solid Waste On Minimisation Of Waste Deposited In Landfills - Dziedzic Krzysztof; Łapczyńska-Kordon Bogusława; Malinowski Mateusz; Niemiec Marcin; Sikora Jakub (Chemical and Process Engineering)
The article discusses an innovative system used for aerobic biostabilisation and biological drying of solid municipal waste. A mechanical–biological process (MBT) of municipal solid waste (MSW) treatment were carried out and monitored in 5 bioreactors. A two-stage biological treatment process has been used in the investigation. In the first step an undersize fraction was subjected to the biological stabilisation for a period of 14 days as a result of which there was a decrease of loss on ignition, but not sufficient to fulfill the requirements of MBT technology. In the second stage of a biological treatment has been applied 7-days intensive bio-drying of MSW using sustained high temperatures in bioreactor. The article presents the results of the chemical composition analysis of the undersize fraction and waste after biological drying, and also the results of temperature changes, pH ratio, loss on ignition, moisture content, combustible and volatile matter content, heat of combustion and calorific value of wastes. The mass balance of the MBT of MSW with using the innovative aeration system showed that only 14.5% of waste need to be landfilled, 61.5% could be used for thermal treatment, and nearly 19% being lost in the process as CO2 and H2O.